PODCAST TO HELP 10th GRADERS UNDERSTAND SPOKEN RECOUNT (RETAIN, 2017)
PODCAST TO HELP 10th GRADERS UNDERSTAND SPOKEN RECOUNT Nadhifa Rahmania S1-Pendidikan Bahasa Inggris, Fakultas Bahasa dan Seni, Universitas Negeri Surabaya nadhifarahmania@mhs.unesa.ac.id Wiwiet Eva Savitri, S.Pd., M.Pd. Pendidikan Bahasa Inggris, Fakultas Bahasa dan Seni, Universitas Negeri Surabaya wiwieteva@unesa.ac.id Abstrak Kemampuanmendengarkandiperolehseseorangbahkansejakberadadalamkandungan.Sayangnyadalamkonteksmempelajaribahasaasing,latihanmendengarkankurangdiberikansecaramaksimalterhadapparapembelajar.Sedangkan proses mendapatkankemampuanberbahasaasingdanbahasaibuberbedadalamprakteknya. Hal ini yang menjadi dasar disusunnya kegiatan diluar kelas untuk melatih kemampuan menangkap makna para pembalajar bahasa asing dan mengasah kemampuan mendengar merekadalam bahasaInggris. Dengan menggunakan pendekatankuantitatif, peneliti memberikan pre-tes dan pos-tes terhadap dua kelompok siswa .Extensive Listening diberikan kepadakelompoksiswa eksperimentaldenganpodcast sebagai media, jugajurnalkegiatanberisipertanyaandanopinipesertaterhadapkegiatantersebut.Jenisteks yang digunakan dalam penelitian ini adalah teks recount yang juga terdapat pada silabus pembelajaran siswa kelas sepuluh. Perbandingan nilai pre-tes dan pos tes peserta menentukan efektifitaspenggunaanpodcast untuk meningkatkan kemampuan mendengarkan peserta dalam bahasaInggris. Secara keseluruhan kelompok eksperimental menunjukkan peningkatan nilai postesjika dibandingkan dengan nilai pre-tes. Berdasarkan hasil tersebut dapat disimpulkan jika penggunaan podcast sebagai media extensive listening untuk kegiatan mandiri siswa cukup efektif meningkatkan kemampuan menangkap makna dalambahasa Inggris. Kata Kunci: Podcast, extensive listening, menangkapmakna, Abstract Listening comprehension is acquired ever since someone was in the womb. Unfortunately in second language learning the practice of listening received by the language learners seems to be insufficient. Meanwhile the acquisition of foreign language and first language are very different in reality. Based on those concerns a set of activity was organized in order to give extra-hours of practice in understanding meaning for the students who master English as foreign language. Using quantitative approach the researcher conducted pre-test and post-test to both groups. An extensive listening activity was directed to the experimental group using podcast as the media that equipped with a listening log. The listening log contains a set of questions related to the podcast files and a section for opinion of the participants towards the proposed activity. The text type used was spoken recount as it also included in the 10th graders syllabus used in the current curriculum. A comparison on the result score of the participant’s pre-test and post-test determined how effective the treatment was. An increasing mean score of experimental group’s post-test showed the improvement of their listening comprehension towards the spoken language. In general, the experimental group performed an improvement of the post-test result compared to the pre-test. Based on the acquired data from the result it can be concluded that the use of podcast as an extensive listening media was affective in improving the learners’ listening comprehension, especially in understanding the meaning. Keywords: Podcast, Extensive Listening, Meaning understanding